Oxidation catalysis by iron and manganese porphyrins within enzyme‐like cages. Issue 10 (22nd February 2018) - Chino, Marco; Leone, Linda; Zambrano, Gerardo; Pirro, Fabio; D'Alonzo, Daniele; Firpo, Vincenzo; Aref, Diaa; Lista, Liliana; Maglio, Ornella; Nastri, Flavia; Lombardi, Angela
Abstract: Inspired by natural heme‐proteins, scientists have attempted for decades to design efficient and selective metalloporphyrin‐based oxidation catalysts. Starting from the pioneering work on small molecule mimics in the late 1970s, we have assisted to a tremendous progress in designing cages of different nature and complexity, able to accommodate metalloporphyrins. With the intent of tuning and controlling their reactivity, more and more sophisticated and diverse environments are continuously exploited. In this review, we will survey the current state of art in oxidation catalysis using iron‐ and manganese‐porphyrins housed within designed or engineered protein cages. We will also examine the innovative metal‐organic framework (MOF) systems, exploited to achieving an enzyme‐like environment around the metalloporphyrin cofactor. Abstract :